Návrh informačního systému pro fitness centrum - Chlebana, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce se zabývá návrhem informačního systému pro fitnes centrum. V práci jsou zpracovány teoretické základy, popsaný a analyzovaný současný stav, popsané hlavní firemní procesy, navržen systém na jejich podporu a ekonomické zhodnocení.

Master's thesis deals with a concept of information system for a gym. In thesis are processed theoretical foundations ,description and analysis of the current situation, describe of the main business processes, a system designed to support this processes and economic appraisals.
Concept of Information System for a Gym
Keywords: Návrh; rezervace; informační systém; SWOT; ERP; proces; Proposal; reservation; information system; SWOT; ERP; process